The Academic Achievement of Tribal Students of Ashram Schools of Surat District - Chaudhari, Priti (JOURNAL OF INDIAN EDUCATION, 2010)
In Indian education system education has limited connotation. It is largely concerned with the existing formal structures of education and the insitutionlised methodology of imparting knowledge to individuals. Within this very system exist many subgroups of individuals with specific needs and tribals are one of them. Education of tribals is an important task before the government of India. One special education input for tribal education is residential schools widely known as Ashram schools in India. These institutions are very special efforts in the direction of tribal education. The study of existing status of education in ashram schools will provide empirical base line about the status of tribal education. Such data also facilitate evaluation of tribal education programmes undertaken. From this point of view it would be worthwhile to know about he academic achivement of tribal students in the ashram schools. The academic achievement of tribal students of Ashram Schools of Surat district was found average in Gujarati, Hindi, Social Science and Mathematics while below average in English and Science and Technology. So there was a need to find out the reasons behind their different levels of achievement in different subjects. The paper shows condition and quality of inputs and the functioning of schools with large ST population is not very encouraging. And there is need to improve the quality of education in ashram schools.